Ultralow-Threshold Continuous-Wave Room-Temperature Crystal-Fiber/Nanoperovskite Hybrid Lasers for All-Optical Photonic Integration - Nguyen, Duc Huy (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.